Severe restless legs syndrome in a family with Alport syndrome - Sparasci, Davide; Rossinelli, Andrea; Ferri, Raffaele; Cippà, Pietro; Rinaldi, Andrea; Manconi, Mauro (BMC nephrology, 2021)
Background Restless legs syndrome (RLS) is a common sleep-related movement disorder characterized by an urge to move the legs during inactivity, especially at evening-night. RLS is highly prevalent in patients with kidney failure and have an impact on quality of life, mood, sleep quality and overall on compliance to the dialysis. Alport syndrome (AS) is a rare inherited disease, predominantly X-linked, secondary to mutations in genes encoding α3, α4 or α5 chains of type IV collagen, and characterized by hematuria, chronic kidney disease, neurosensory deafness, and lenticonus. Case presentation Here we describe a family with a combination of X-linked AS and severe RLS accompanied by periodic limb movements during sleep (PLMS). In the first patient we identified, RLS was complicated by a paradoxical response to dopamine agonists named “augmentation”, leading to sleep disruption, hallucinations and five peritoneal perforations during the peritoneal dialysis due to the difficulty to rest still. Therapeutic adjustments and renal transplantation improved RLS and PLMS. In two brothers, severe RLS prevented a compliance with hemodialysis. Female family members carrying the mutation were also affected by RLS, while those without the mutations were RLS-free. Conclusions RLS has not been reported earlier in association with AS, but the peculiar combinations observed in this family will stimulate further clinical studies and motivate nephrologists to seek for RLS symptoms and sleep disturbances in AS patients.